Modulating the anodic electrochemiluminescence of graphitic carbon nitride by thiophene doping. (4th August 2022) - Chen, Lichan; Zhao, Panpan; Tian, Libing; Wang, Yini; Zhou, Shu-Feng
Abstract : Modulating the anodic electrochemiluminescence of graphitic carbon nitride by molecular engineering with electron donor thiophene. Abstract : As an attractive electrochemiluminescence (ECL) emitter, graphitic carbon nitride (g-CN) still suffers from weak anodic ECL signals. In this work, a simple molecular engineering strategy is employed to modulate the anodic ECL of g-CN by thiophene doping. Thiophene doped g-CN (CNA) nanosheets show ca. a 6-fold enhanced and red-shift ECL emissions compared to pristine g-CN nanosheets. The optical and ECL property studies reveal that thiophene doping can not only evaluate g-CN electric conductivity by intramolecular electron transfer but also narrow the bandgap, leading to the enhancement and bathochromic shift of ECL emissions. The effects of various factors including the thiophene doping amount, solution pH, coreactant concentration and adopted potential range on the anodic ECL of CNA nanosheets are further investigated for understanding the mechanism of ECL enhancement and obtaining a strong and stable anodic ECL emission. On this basis, the CNA nanosheets modified electrode is used as a signal probe for Cu 2+ detection, and the probe shows a linear response to Cu 2+ in the concentration range of 5 nM to 50 μM and high selectivity towards other possible interfering metal ions. Our work may provide a promising pathway for the modulation of g-CN ECL by molecular engineering, and the improved anodic ECL may promote its sensing application.